2001
DOI: 10.1111/0272-4332.216176
|View full text |Cite
|
Sign up to set email alerts
|

Application of Monitoring Data forGiardia andCryptosporidium to Boil Water Advisories

Abstract: Despite the problems associated with analyzing water samples for Giardia cysts and Cryptosporidium oocysts, the data can be very useful if their strengths and weaknesses are understood. Two municipalities in northern Ontario, Temagami and Thunder Bay, both issued boil water advisories for Giardia contamination. Data from these two cities are compared to show that only one municipality experienced a real outbreak, whereas the other did not. The concentration of Giardia cysts was much higher than background duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The prevalence of 0.05% in our human faecal samples is comparatively lower and suggests that Giardia shedding on PEI is rare. In Canada, several human G. duodenalis outbreaks have been reported in the last two decades (Wallis et al., 2001) with the most predominant genotype being assemblage A (Caccio and Ryan, 2008). The exclusive detection of assemblage A in this study is consistent with the predominant occurrence of this assemblage in Canada.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of 0.05% in our human faecal samples is comparatively lower and suggests that Giardia shedding on PEI is rare. In Canada, several human G. duodenalis outbreaks have been reported in the last two decades (Wallis et al., 2001) with the most predominant genotype being assemblage A (Caccio and Ryan, 2008). The exclusive detection of assemblage A in this study is consistent with the predominant occurrence of this assemblage in Canada.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that effective levels to outbreaks with these protozoa ordinarily occur when oocyst concentrations raised to 5 Giardai cyst in 100 liters of water sampled (4,5) and 10 to 30 oocysts for Cryptosporidium (6). Detection of low numbers of organisms in water samples is difficult, it needs very sensitive techniques.…”
Section: Introductionmentioning
confidence: 99%
“…These infections are associated with endemic infection rates in many jurisdictions but they have also caused large outbreaks [5,6]. In Canada, several outbreaks have been reported in recent decades due to Cryptosporidium parvum [7,8] and Giardia lamblia [9]. Population-based surveillance studies conducted in the United States have demonstrated increasing rates for giardiasis between 1992–97 with the highest national rates being amongst children aged 0–5 years, followed closely by persons aged 31–40 years [1,10-12].…”
Section: Introductionmentioning
confidence: 99%